Exporting: Does Sales Volume Make a Difference? — Comment - Reid, Stan D. (Journal of International Business Studies, 1985)
This paper examines a recent investigation of the relationship between firm size and exporting. It illustrates how and why neglect of critical conceptual and methodological issues continues to confound research on the impact that firm size has on exporting.